2020
DOI: 10.1080/21645515.2020.1832408
|View full text |Cite
|
Sign up to set email alerts
|

Need for hepatitis A prevention in patients with chronic liver disease in the changing epidemiological setting of India

Abstract: The burden of chronic liver disease (CLD) in India is high, particularly among middle-aged men, with nearly 220,000 deaths due to cirrhosis in 2017. CLD increases the risk of infection, severe disease (e.g. hepatitis A virus or HAV superinfection, acute-on-chronic liver failure, fulminant hepatic failure), and mortality. Hence, various countries recommend HAV vaccination for CLD patients. While historic Indian studies showed high seroprevalences of protective HAV antibodies among Indian adults with CLD, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Immunogenicity of hepatitis A Vaccine in CLD: Currently approved vaccinations against HAV include Havrix and Vaqta. While regulatory bodies in the UK and USA recommend HAV vaccine in those with CLD, in certain countries like India, where the prevalence of HAV antibodies in CLD is reportedly greater than 90%, routine vaccination is not recommended 81 . The safety and efficacy of HAV vaccines in CLD are well documented 82 , 83 .…”
Section: Hepatitis a Vaccinementioning
confidence: 99%
“…Immunogenicity of hepatitis A Vaccine in CLD: Currently approved vaccinations against HAV include Havrix and Vaqta. While regulatory bodies in the UK and USA recommend HAV vaccine in those with CLD, in certain countries like India, where the prevalence of HAV antibodies in CLD is reportedly greater than 90%, routine vaccination is not recommended 81 . The safety and efficacy of HAV vaccines in CLD are well documented 82 , 83 .…”
Section: Hepatitis a Vaccinementioning
confidence: 99%
“…Among HCPs, it has been shown that seropositivity for anti-HAV antibodies through previous exposure can vary because of factors including age, education, occupation, income and socio-economic class [ 44 ]. However, in India, a decline in infection rate in children due to improved living conditions has led to an increase in susceptible adults, who are more likely to have severe morbidity and mortality if not exposed in childhood [ 45 – 47 ]. This is highlighted by HAV outbreaks that have disproportionately affected adolescents and adults compared with children [ 48 ].…”
Section: Vpds and Their Impact On Hcps Across Indiamentioning
confidence: 99%